2015
DOI: 10.1186/s12990-015-0004-7
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally Increased Artemin is a Key Regulator of TRPA1/V1 Expression in Primary Afferent Neurons

Abstract: BackgroundArtemin, a member of the glial cell line-derived neurotrophic factor family, is known to have a variety of neuronal functions, and has been the subject of attention because it has interesting effects, including bi-directional results in modulation in neuropathic and inflammatory pain. It has been shown that the overexpression of artemin is associated with an increase in the expression of TRP family channels in primary afferents and subsequent hyperalgesia, and an increase in neuronal activity. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 42 publications
2
59
2
Order By: Relevance
“…Similarly, GFLs potentiate capsaicin responses in dissociated DRG neurons recorded by Ca 2+ imaging, showing sensitization of TRPV1 + cells (45). However, specific changes in TRPV1 channel activity have not been reported, and the preponderance of data suggests that artemin-induced heat hyperalgesia is caused by increased TRPV1 expression (27,28,46,47). Moreover, unlike the established TRPM8 dependence of arteminand NGF-evoked cold allodynia (8) or the necessity of TRPV1 for NGF-induced heat hyperalgesia (36), the molecule determinants of GFL-evoked alterations in nociception in vivo are unknown (48).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, GFLs potentiate capsaicin responses in dissociated DRG neurons recorded by Ca 2+ imaging, showing sensitization of TRPV1 + cells (45). However, specific changes in TRPV1 channel activity have not been reported, and the preponderance of data suggests that artemin-induced heat hyperalgesia is caused by increased TRPV1 expression (27,28,46,47). Moreover, unlike the established TRPM8 dependence of arteminand NGF-evoked cold allodynia (8) or the necessity of TRPV1 for NGF-induced heat hyperalgesia (36), the molecule determinants of GFL-evoked alterations in nociception in vivo are unknown (48).…”
Section: Discussionmentioning
confidence: 99%
“…contr, Contralateral; ipsi, ipsilateral; ns, not significant; oxal, oxaliplatin. ***P < 0.001. hyperalgesia as well as altered expression of molecules involved in sensory transduction (27,28). However, these studies involved either genetically induced artemin overexpression in the periphery (27) or multiple plantar injections of exogenous artemin (28), making it unclear if artemin-GFRα3 signaling influences afferent expression phenotypes under physiological conditions.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Some study reports showed that expression changes of TRP channel protein super-family members in dorsal root ganglion can also affect peripheral pain perception, 21 which will be the focus of our further research. Meanwhile, the time points we selected for determining pain thresholds and measuring TRPA1 and TRPV4 expression levels of each group were one week before modeling, and two, four, six, and eight weeks after modeling, respectively, since two weeks are required for successful modeling and eighth week after modeling was the last time TRPA1 and TRPV4 inhibitors were applied.…”
Section: Discussionmentioning
confidence: 97%